APORTES DESDE LA GEOGRAFÍA PARA EL ESTUDIO DE LA CALIDAD DE VIDA EN LA PATAGONIA ARGENTINA A PRINCIPIOS DEL SIGLO XXI - Pérez, Germán Gabriel; Mare, Marcos Damián; Velázquez, Guillermo (Caderno de Geografia, 2022)
In this article, the Quality of Life Index (QLI) is used to analyze the socio-economic and environmental differences, at the census radius scale, of the population of Argentine Patagonia, a territory that, despite leading the national QLI ranking, has significant internal differences. The results obtained show 12 Areas of Relative Homogeneity distinguished by their internal characteristics and qualities of the regional organization. The variables related to the quality of life show different situations. Among them, one highlight: a) differentiation between rural spaces with a large surface area and a low population concerning urban areas that structure regional dynamism, b) significant fragmentation in urban peripheries in a context of great demographic dynamism, c) enclaves of exploitation of energy, mineral and tourist resources and d) intermediate cities with administrative and financial weight. All these disparities confirm the idea of a highly heterogeneous Argentine Patagonia.